Highlights 2017 - Yearly status report EDEN Initiative - Schubert, Daniel; Zabel, Paul; Zeidler, Conrad; Vrakking, Vincent (2017)
December 17th - CapeTown - South Africa: The EDEN team finishes its last preparations for the upcoming EDEN ISS mission. The next day, the adventure will begin with the inbound flight to the Russian Novo Airbase; Location: Antarctica. From there, the team flies to the German Neumayer Station III, the group’s new test ground for the developed closed-loop greenhouse system. Four years of intense planning, hardware development, testing and enhancements finally brought the EDEN team to the eve of the start of the long-awaited Antarctic mission. For the next eight weeks, the team will pick up the EDEN ISS Mobile Test Facility at the shelf ice and then build up the system in the vicinity of the station. The year 2017 marked an extraordinary year, as all essential controlled environment agriculture subsystems were integrated into the EDEN ISS greenhouse system. Located in the backyard of the DLR Institute of Space Systems in Bremen (Germany), the container was the place of intensive work, where the EDEN team and its consortium partners successfully accomplished all important assembly, integration, and test (AIT) procedures. Then from May until September, the greenhouse system provided suitable conditions for plant growth so that several test grow-outs could be performed. In June, the successfully organized Flight Readiness Review (FRR) marked an important milestone for the EDEN team. The European Union and the scientific advisory board gave a green light for the planned analogue test mission. An additional highlight of the year were the kick-offs of the two projects PMARS and GERF, which are both funded through the German Ministry of Research (BmBF). With partners, located in Morocco and Egypt, the projects foresee the adaptation and transfer of EDEN’s developed greenhouse technologies into terrestrial systems, in order to provide a closed-loop food production system in desert and arid areas. The EDEN team looks forward to proceeding with the upcoming research tasks in 2018. Through the Antarctic mission and the ...